Teaching of Speaking Skill with Picture Expression Strategy at the Islamic Boarding School/تعليم مهارة الكلام باستراتجية التعبير المصور في المعهد العصري الإسلامي - Barokah, Anisatul; Rizqiyah, Zamronah (UIN Raden Mas Said Surakarta, 2020)
The purpose of this study was to determine the implementation of the strategy atta'bir almushawwar using the book Muthala'ah alqiro'ah al-rosyidah and to determine the increase in speaking skills. This research uses qualitative research. This research was carried out from June to August 2019 at the Islamic Boarding School Ta'mirul Surakarta. The data collection techniques are through the interview, observation, and documentation techniques. And the data validity technique uses triangulation of sources and methods. And data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the steps of atta'bir almushawwar using the Muthala'ah alqiro'ah al-rosyidah book, namely the teacher reads the vocabulary aloud and students follow it, and the teacher asks students to interpret it, the teacher asks the students to listen to the teacher's explanation with Image media are on the board and in a situation where students do not open the book, the teacher asks students to read muthalaah books and then gives students time to ask questions about vocabulary or things that have not been understood, the teacher asks some students to retell what the teacher has explained in front of the class by using Arabic. By using the attakbir almushawwar strategy in learning the muthalaah book, it is very helpful for students to remember the material that has been explained by the teacher. Because the explanation using image media makes students interested students pay attention to the scale of what is explained by the teacher. And in addition, students have to memorize again using Arabic that they have understood, with this students are trained in speaking and can increase students' speaking skills